Coarse ware from Bregenz/Brigantium: An approach to the type range of the first half of the 1st century AD - Oberhofer, Karl (Rei Cretariae Romanae Fautorum Acta, 2022)
Summarising the research done so far, the knowledge of coarse ware from Brigantium is comparatively good for the first half of the 1st century AD. Regarding the grave complexes published by Carl von Schwerzenbach und Johannes Jacobs in 1911, stratified sherds from the military forts now allow a quite precise temporal classification. Especially from the surrounding of the porta principalis sinistra of the Tiberian military fort the material basis is scientifically convincing with regard to the quantity and quality of the ceramic finds. In the earliest decades of Brigantium the Roman influence on the coarse ware was stronger than in the second half of the 1st century. Unpretentious bowls and tons in a strong Latènetradition representing indigenous ceramic forms are present in very small quantity. The well-known black engobed bottles in the Latène tradition are missing completely – instead single and double handled jars were in use in the vicinity of the military forts. Storage pots of the predominant local tradition were made with a black or dark grey engobe and were accompanied by dolia and imported urcei. Mainly handmade (as opposed to wheel thrown) cooking pots confirm that the general evolution was similar to that of Vindonissa and Zurzach.